Enhancing laying performance and immunity via probiotic and vitamin additives during induced molting - Wang, Chunyang; Xiao, Sa; Yang, Zengqi (Frontiers in Veterinary Science, 2024)
Introduction Molting is induced in commercial laying hens to rejuvenate the reproductive system and increase egg production. However, this process causes stress and reduces bird health and performance. Methods The experiment was conducted to study the effect of multi probiotics and vitamin additives on induced molting in 240 ISA Brown hens. Hens were randomly divided into four groups receiving probiotic and vitamin additives (I–IV) during different period of molting. During the whole molting process, the laying performance indexes such as egg laying rate, egg quality, ovary weight and oviduct lengths were measured, and the spleen index, serum immunoglobulin, immune response of NDV and AIV vaccine were monitored. Results Molted hens resumed 50% egg production in just 37 days, with 1.62% mortality. Egg quality such as egg weight, yolk color, Haugh unit, eggshell strength and protein height were significantly improved. After the second production peak, the reproductive organs and immune organs returned to normal, and the immune antibody titer of NDV vaccine increased significantly. Discussion Molting with probiotic and vitamin additives improve the laying performance and egg quality, reduce mortality, significantly improve immune function and vaccine titer, and help to enhance disease resistance and maintain production performance of aged laying hens.